Organizing the Bench: Medical Laboratory Workers in the Maritimes, 1900--1950. - Twohig, Peter Lawrence (Dalhousie University, 1999)
Medical laboratory technology is the third largest health profession in Canada. Yet, these workers are largely invisible, both to the public and historiographically. Even recent studies of laboratory medicine make only fleeting reference to workers at the bench. This study examines the origins of the laboratory workforce at the Pathological Institute in Halifax in particular, and the Maritime provinces more generally. It utilizes hospital, university and archival records to demonstrate how this workforce was created as part of a "health care team" and the implications this had for the workers themselves. As Canadian hospitals grew in number and bed capacity over the opening decades of the twentieth century, they also grew in complexity. Hospitals added new services, including departments such as dietetics, x-ray and expanded laboratory facilities. As these services matured, the routine work passed from physicians working alone to specially trained workers. Yet, this process was not uniform and remained remarkably incomplete. In the first half of the twentieth century, laboratory workers did not share a common education, training experience, or labour process. Hospital workers in the Maritimes and elsewhere did not necessarily perform discrete tasks and many, notably nurses, assumed duties in the laboratory. The workers themselves had diverse educations and work experiences. Well into the 1950s, the "laboratory worker" was a diffuse concept. The demands of patients and physicians for enhanced services, the constraints of budgets, recruitment and retention problems, and the interests and desires of workers themselves combined to shape laboratory work. Viewed from the laboratory, the story of the twentieth century Canadian hospital is not one of ever-expanding specialization, but rather a complex milieu where the social relations of skill and gender found bold articulation.